Inferring floor area ratio thresholds for the delineation of city centers based on cognitive perception. (February 2021) - Wurm, Michael; Goebel, Jan; Wagner, Gert G; Weigand, Matthias; Dech, Stefan; Taubenböck, Hannes
The morphology of today's cities is the result of historic urban developments and on-going urban transformation resulting in complex urban spatial structures. While functionally as well as spatially, cities are structured into sub-units such as the city center, business districts, residential areas, or industrial and commercial zones, their precise localization in the geographic space is sometimes difficult. City centers in particular are difficult to grasp because they stand for many different urban functions. Generally, they are characterized as areas of high densities, such as employment, population, or commerce, but also as areas of high structural densities. In past studies, various approaches, data, and cut-off values have been presented to separate city centers from the surrounding transition zones in geographical information systems based on density values. To overcome the difficulty in defining the right density threshold, the current study presents an approach which integrates the subjective perception of citizens on the urban spatial structure and relates it to the floor area ratio to delineate city centers to infer a characteristic density threshold. In a large empirical study of 67 monocentric cities in Germany, we observe a decreasing floor area ratio gradient toward the urban fringes. The result of the study reveals a relative threshold for city centers at around 30% of the density of the "central place."